Governance of the Sustainable Public Palm Oil Replanting Program (PSR) in Riau Province - Mayarni Maya; M. Y Tiyas Tinov; Adianto Adianto; Hasim Asari (Universitas Sultan Ageng Tirtayasa, 2022)
The concept of good governance is a reference concept that is recognized as being a good manager of government activities. Governance is governance, administration, or management which can be interpreted as power that is no longer owned or becomes a matter for the government. The purpose of this study was to find out how the governance of the sustainable PSR program in Riau Province is. The research method used is qualitative research with a case study approach. The results of this study show that the governance of the sustainable PSR program in Riau Province has been going well but still has some challenges in its distribution and distribution. The challenges identified in this research are the 2019 Coronavirus disease, human resources, and the increasing price of palm oil.